Faecal calprotectin: current usage and perceived beneficial effects of third‐party funding on rates of colonoscopy by Australian gastroenterologists. Issue 5 (May 2016) - Elnawsra, O.; Fok, I.; Sparrow, M.; Gibson, P.; Andrews, J.; Connor, S.
Abstract : Background: Studies have suggested a diagnostic role for faecal calprotectin (FC) in patients with gastroenterological disorders. Aim: To investigate Australian gastroenterologists' (GE) views on FC use and to elicit factors that affect physicians' choices. Methods: Electronic surveys were sent out to 405 consultants and 34 registrars in Australia. Respondents who answered <50% of the survey were excluded. Results: In all, 140 participants provided a >50% response; 73% reported using FC in their clinical practice. Factors cited by non‐users in restricting their FC use included cost (24%), availability (47%) and familiarity (18%). Even among users, 69% cited funding as a major deciding factor; 98 and 86% of FC users believed that the test is a reliable method of differentiating between inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS) and assessing for mucosal healing in IBD respectively. Of non‐users, 78 and 58%, respectively, would use FC to differentiate IBD from IBS and assess for mucosal healing in IBD, if FC testing was Medical Benefits Schedule (MBS) listed. Both users (79%) and non‐users (68%) reported that use of FC to defer or avoid colonoscopies was likely if the test was MBS funded. Conclusion: Australian GE endorse the use of FC to discriminate between IBD and IBS, to check for mucosal healing in IBD and to reduce colonoscopy rates. Absence of MBS funding is an important factor contributing to the lack of usage of FC, in addition to the lack of familiarity with FC testing and availability.